Makna Bisnis Online Oleh Pengusaha Muda Di Kecamatan Randuagung Kabupaten Lumajang - Rusmini, Rusmini (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2021)
The background of the formation of this research is based on the phenomenon of the shift in the use of telecommunication media, apart from being social media, it is also capable of being a marketing medium and introducing products, with internet facilities not only as a center for exchanging information. The concept formed on the internet that includes global village is Social Media. Where the use of social media has been able to be used as a tool or online business media for youth, especially the people of Randuagung, Lumajang Regency, while starting a business. The purpose of this research is to find a motive, meaning and experience of communication by a young entrepreneur in starting and building an online business on social media. The final results of this study indicate that the motives of young entrepreneurs in doing online business are increasingly diverse, as evidenced by the lack of conventional businesses and even fewer visitors, while online businesses are able to reach more potential buyers. The meaning of online business by young entrepreneurs is based on the principle of trust between business people, so that positive and negative communication experiences are formed.